Evaluation of Completeness of Operative Records in Women Undergoing Gynecologic Surgery at Chiang Mai University Hospital - Natnita Mattawanon; Narisa Sribanditmongkol; Jatupol Srisomboon; Chumnan Kietpeerakool (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To evaluate the completeness of operative records at the general gynecologic surgery unit using the Good Surgical Practice (GSP) 2008 guidelines as a gold standard.Materials and methods: The operative records of women undergoing gynecologic operation at Chiang Mai University Hospital between January and July 2009 were reviewed. According to GSP 2008, the operative record should include all of the following data: (1) date and time of operation; (2) types of surgery ; (3) name of the operating surgeon and assistant; (4) operative procedure carried out; (5) incision; (6) operative diagnosis; (7) operative findings; (8) operative complications; (9) any extra procedure performed and its reason; (10) details of tissue removed, added or altered; (11) identification of any prosthesis used including serial numbers of such materials; (12) details of closure technique; (13) postoperative care instruction and (14) a signatureResults: During the study period, the medical records of 232 women who underwent gynecologic surgery were reviewed to determine the quality of the operative record. Postoperative care instruction was completely recorded in all operative notes (100%). Only 2 of the 14 items failed above 10% including details of incision (10.3%) and details of closure technique (12.9%). The signature was absent in 13 operative notes (5.6%).Conclusion: The evaluation results of operative records as per GSP 2008 guidelines in this study appear to be favorable. The details of incision and closure technique should be improved and periodic audit is required to assure that these standards are maintained.